10
$\begingroup$

Question:

Does $\triangle ABC$ exist such that $\triangle ABC \sim \triangle DEF$, with $D, E, F$ being the incentre, centroid, orthocentre of $\triangle ABC$, resp.?

For such a triangle to exist, it must be obtuse. Besides that, I have no idea how to prove or disprove it. For the case of $D, E, F$ being the orthocentre, centroid, circumcentre, it's impossible as they lie on the same line (Euler's line). That's the motivation of the problem. I have a feeling that brute force methods are needed (coordinate geometry). But I hate such an ugly approach. Any idea?

$\endgroup$
6
$\begingroup$

Yes, this triangle exists. (Found using brute force approximation.)

similar triangles

Coordinates: $$A\approx(0.182,0.260)\quad B=(0,0)\quad C=(1,0)\\ D\approx(0.229,0.120)\quad E\approx(0.394,0.087)\quad F\approx(0.182,0.571)$$

Angles: $$a=d\approx107.2957\quad b=e\approx55.0744\quad c=f\approx 17.6299$$

$\endgroup$
1
$\begingroup$

Here's what I mean by a brute force approach:

Without loss of generality, let's choose an appropriate scale such that $AB=1$.

Set

$$A=(0,0)$$ $$B=(1,0)$$ $$C=(x,y)$$

Then the coordinate of the centroid $E$ is

$$E=\left(\frac {x+1}{3},\frac {y}{3}\right)$$

To find out the coordinate of the incentre $D$, let's calculate the side lengths and perimeter $P$ first

$$|AB|=1$$ $$|AC|=\sqrt{x^2+y^2}$$ $$|BC|=\sqrt{(x-1)^2+y^2}$$ $$P=AB+AC+BC=1+\sqrt{x^2+y^2}+\sqrt{(x-1)^2+y^2}$$

Then the coordinate of the incentre D is

\begin{align} D &=\frac{|BC| A + |AC| B + |AB| C} { P } \\ &= \left (\frac { \sqrt { x ^ { 2 } + y ^ { 2 } } + x} {1 + \sqrt { x ^ { 2 } + y ^ { 2 } } + \sqrt { ( x - 1 ) ^ { 2 } + y ^ { 2 } }} , \frac{y}{1 + \sqrt { x ^ { 2 } + y ^ { 2 } } + \sqrt { ( x - 1 ) ^ { 2 } + y ^ { 2 } }} \right) \end{align}

The coordinate of the orthocentre $F(a,b)$ satisfies

$$\left\{ \begin{aligned} \frac{b}{a-1} &=-\frac{x}{y} \\ a&=x \end{aligned} \right.$$

Hence $$F=\left(x, \frac{x-x^2}{y}\right)$$

By similarity

$\frac{DE}{BC}= \sqrt { \frac { \left( \frac { x + 1 } { 3 } - \frac { \sqrt { x ^ { 2 } + y ^ { 2 } + x } } { 1 + \sqrt { x ^ { 2 } + y ^ { 2 } } + \sqrt { ( x - 1 ) ^ { 2 } + y ^ { 2 } } } \right) ^ { 2 } + \left( \frac { y } { 3 } - \frac{y}{1 + \sqrt { x ^ { 2 } + y ^ { 2 } } + \sqrt { ( x - 1 ) ^ { 2 } + y ^ { 2 } }} \right) ^ { 2 } } { ( x - 1 ) ^ { 2 } + y ^ { 2 } } }$

$=\frac{EF}{AC}=\sqrt{\frac{\left(\frac { x + 1 } { 3 }-x \right)^2 + \left(\frac { y } { 3 }-\frac { x - x ^ { 2 } } { y } \right)^2}{ x ^ { 2 } + y ^ { 2 } }}$

$=\frac{DF}{AB}=\sqrt{\left(\frac { \sqrt { x ^ { 2 } + y ^ { 2 } } + x } { 1 + \sqrt { x ^ { 2 } + y ^ { 2 } } + \sqrt { ( x - 1 ) ^ { 2 } + y ^ { 2 } } }-x\right)^2+\left(\frac { y } { 1 + \sqrt { x ^ { 2 } + y ^ { 2 } } + \sqrt { ( x - 1 ) ^ { 2 } + y ^ { 2 } } }-\frac { x - x ^ { 2 } } { y }\right)^2}$

And I've no idea how to solve it with bare hands. Feel free to complete my answer. I'm curious whether there is a purely geometric approach (maybe non-constructive).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.